Race, space and riots in Chicago, New York and Los Angeles - Abu-Lughod, Janet L. (Oxford University Press, 2007)
An overview of race riots in New York, Chicago and Los Angeles -- The bloody riot of 1919 and its consequences -- The black uprising after King's assassination in 1968 -- The Harlem revolts of 1935 and 1943 -- The Harlem-Bedford Stuyvesant uprising of 1964 -- The Watts rebellion of 1965 -- Riot redux : South Central, 1992 -- Explaining differences, predicting convergence